Lung cancer risk among hairdressers in SYNERGY – pooled analysis from case-control studies in Europe and Canada. (19th October 2011) - Olsson, Ann; Guha, Neela; Brüning, Thomas; Pesch, Beate; Kendzia, Benjamin; Wichmann, Heinz-Erich; Brüske, Irene; Stücker, Isabelle; Pesatori, Angela Cecilia; Landi, Maria Teresa; Caporaso, Neil; Siemiatycki, Jack; et al.
Abstract : Objectives: Most cohort studies show an increased risk of lung cancer among hairdressers. We investigated the risk of lung cancer among hairdressers and barbers in a large pooled dataset, while controlling for smoking. Methods: The SYNERGY project has pooled information on lifetime work histories (ISCO-68) and tobacco smoking from 16258 lung cancer cases and 19922 controls, including 20% women, from 12 case-control studies in European and Canada. ORs for lung cancer and 95% CIs were estimated by unconditional logistic regression, adjusted for age, sex, study, cigarette pack-years and time since quitting smoking. Results: Less than 1% of the study population had ever worked as hairdresser or barber (145 cases, 140 controls). Hairdressers and barbers experienced a slight increase in lung cancer risk (OR 1.23; 95% CI 0.97 to 1.56), which disappeared after adjusting for smoking (OR 0.95; 95% CI 0.72 to 1.25). Results by duration of employment showed highest risks in hairdressers with short employment. Results were similar by gender and histology of lung cancer. We observed a slight and non-significant increase in risk for male barbers, particularly in barbers with the longest employment and after adjustment for smoking (OR 1.62; 95% CI 0.81 to 3.24). Conclusions: We did not detect an increased risk of lung cancer overall among those who ever worked as hairdresser or barber. However, among male barbers we observed that risk increased with duration of employment, although not statistically significant.